Hydrogen and syngas production through dynamic chemical looping reforming-decomposition of methane. (26th February 2022) - Nourbakhsh, Hessamodin; Khani, Yasin; Zamaniyan, Akbar; Bahadoran, Farzad
Abstract: This work introduces CeZr0.5 GdO4 spinel particles as novel oxygen carriers for use in the reforming and decomposition of methane into H2 and CO via the chemical looping technique. These particles were prepared by a modified sol-gel combustion method to increase their reactivity by increasing the surface area and consequently more accessibility of the gas feed to the solid phase. The performance of the synthesized materials was dynamically evaluated in terms of activity and stability at different operating temperatures (800–900 °C). The air used in the oxidation step eliminates almost all of the deposited solid carbon and converts it to CO, while providing the oxygen consumed in the reduction step. Oxygen carrier particles showed a conversion of more than 90% in all cycles after about 30 min of reduction operations. By the optimal operating path proposed in this research, more than 90% of the reactor exhaust gas is allocated to the production of H2 and CO with almost complete elimination of CO2 and H2 O in a shorter period of time. This will also reduce the time required for coke gasification and lattice oxygen replenishment of the spinel. Finally, the CeZr0.5 GdO4 proved to be a successful oxygen carrier for the continuous production of hydrogen and carbon monoxide with almost no remarkable reduction in activity during successive redox cycles. Graphical abstract: Image 1 Highlights: Chemical looping reforming (CLR) of methane has been investigated. CeZr0.5 GdO4 spinel was synthesized as a new oxygen carrier for CLR process. High-purity H2 production was experimentally obtained using successive redox cycles. Solid carbon can be well eliminated by gasification reactions occurred in the process. Optimal operating conditions were proposed for maximum production of H2 and CO.